Obstacles Faced by African Copreneurs in Black Townships of the Western Cape, South Africa - Myeko, Zolile; Iwu, Chux Gervase (Journal of Reviews on Global Economics, 2019)
The primary objective of this study is to examine the experiences of copreneurs specifically those who operate in the black townships of the Western Cape. Specifically, this study targets African1 copreneurs. Copreneurship is the term used when a husband and wife come together to own and manage a business as part of their daily engagement. As copreneurs, they confront specific obstacles. In South Africa, copreneurs exist within the framework of two fields, namely small, medium, micro business and family business. This study adopts a mixed research methodology, involving both quantitative and qualitative techniques. Thus the data collection instruments included a questionnaire and an interview schedule involving 150 subjects. The findings reveal, among other things, that major obstacles include the lack of finance for business expansion, as well as the lack of relevant information about government support, crime and absence of infrastructure. This study provides an opportunity to understand the specific challenges that c face, as well as information about the state of African copreneurship in black townships in the Western Cape. It is hoped that the findings and recommendations will shine a light on the specific challenges, as well as provide the necessary remedial opportunities so that these entrepreneurs are able to meaningfully add value to their respective communities.